7-Day Nonbismuth-Containing Concomitant Therapy Achieves a High Eradication Rate for Helicobacter pylori in Taiwan. (22nd July 2012) - Kao, Sung-Shuo; Chen, Wen-Chi; Hsu, Ping-I; Lai, Kwok-Hung; Yu, Hsien-Chung; Cheng, Hui-Hwa; Peng, Nan-Jing; Lin, Chiun-Ku; Chan, Hoi-Hung; Tsai, Wei-Lun; Wang, Huay-Min; Tsai, Tzung-Jiun; et al.
Abstract : Background. Ten-day concomitant therapy achieves a high eradication rate in Taiwan. Whether shortening the duration of concomitant therapy can still keep a high eradication rate remains unclear. Aim. To assess the eradication rate of 7-day pantoprazole-containing concomitant therapy in Taiwan and to investigate factors influencing the eradication outcome. Methods. From March 2008 to March 2012, 319 H. pylori -infected patients receiving a 7-day pantoprazole-containing concomitant regimen (pantoprazole 40 mg, amoxicillin 1 g, clarithromycin 500 mg, and metronidazole 500 mg twice daily for 7 days) were included. Patients were asked to return at the second week to assess drug compliance and adverse effects. Repeated endoscopy or urea breath test was performed at 8 weeks after the end of eradication therapy. Results. The eradication rates according to intention-to-treat and per-protocol analyses were 93.7% (299/319) and 96.4% (297/308), respectively. Adverse events occurred in 13.2% (42/319) of the patients. The compliance rate was 98.4% (314/319). Multivariate analysis disclosed that poor compliance was the only independent factor influencing the efficacy of anti- H. pylori therapy with an odds ratio of 0.073 (95% confidence interval, 0.011–0.483). Conclusion. 7-day concomitant therapy achieved a very high eradication rate for H. pylori infection in Taiwan. Drug compliance was the only clinical factor influencing treatment efficacy.